KEMURNIAN KETURUNAN MENGGUNAKAN MARKA SSR SEBAGAI SISTEM KONTROL DAN SELEKSI DINI KELAPA SAWIT (Elaeis guineensis JACQ.) - Rokhana Faizah; Sri Wening; Abdul Razak Purba (Pusat Penelitian Kelapa Sawit, 2017)
Information of legitimacy of oil palm progenies is important to guaranty the quality and to control commercial seeds procedures. A true and legitimate cross will produce progeny which has a combination of their parent's allele. The information could be obtained early in the nursery stage through DNA fingerprinting analysis. Simple Sequence Repeats (SSR) is one of DNA markers used for DNA fingerprinting, since the marker system has advantages to acquire information of allele per individual in population and efficiency diverse allele of progeny and their parents. The aim of the research is to obtain legitimacy of 12 progenies analyzing in the oil palm nursery stage. Thirteen SSR markers were used to analyze 12 crossings number of oil palm. The genotypes data by alleles of SSR inferred and quantified using Gene Marker® Software version 2.4.0 Soft Genetics® LLC and analyzed based on Mendel's Law of Segregation. The result showed based on heredity pattern of progeny and their parent's allele that progenies H were indicated genetically derived from their known parents while progenies from A and G indicated as illegitimate crossing. Probability value for legitimacy of progenies of 9 other crosses has 0.031 and 0.5. Legitimacy analysis of progeny using SSR markers could be used to control the quality of crossing material and earlier selection in the oil palm nursery.